Pedagogy of nonviolence as a principle of humanistic pedagogy - Galina V. Tuguleva; Inessa V. Kashuba; Marina V. Romanova; Veronika V. Tsurkan; Nuria M. Rakhimova; Svetlana S. Velikanova (Revista on line de Política e Gestão Educacional)
A modern teacher is obliged to build relationships with students on mutual trust, on a nonviolent basis, is to accept the goals and interests of children, create conditions for realizing and developing their full potential and forming the personality as a whole. The present article is concentrated on the problem of formation of the position of nonviolence among students majoring in teaching training in the process of their professional training at higher school.  To gratify the aim of the study, theoretical-analysis, generalization, systematization, synthesis, modeling; and empirical – conversation, observation, quantitative and qualitative methods are utilize. The paper provides the author’s complex of pedagogical conditions that ensure the formation of a position of nonviolence among pedagogical specialty students in the process of their professional training in a higher educational institution and describes the results of experimental work that has confirmed the hypothesis put forward.